Perilaku Tidak Memilih Dalam Pemilihan Kepala Desa Kote Kabupaten Lingga Tahun 2021 - Farahul Intihan; Bismar Arianto; Eki Darmawan (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
The implementation of democracy at the village level can be proof that political development in Indonesia has developed rapidly by involving local communities, so that they are able to carry out the functions of regional government power in order to achieve the goal of advancing and prospering people's lives. Non-voting behavior are a group of people who are unwilling and negligent in giving their voting rights in elections for various reasons, whether in legislative elections, regional elections, presidential elections or village head elections. Non-voting behavior are also called blanks or abstentions in elections that are limited to an organization, company or institution. Voter absence at an election is closely related to voter dissatisfaction or satisfaction. In Kote Village, non-voting behavior has a large number compared to other villages in Singkep Pesisir District. The existence of this phenomenon certainly has a cause for non-voting behavior by the Kote Village Community. The aim of this research is to determine the factors causing non-voting behavior in Kote Village, Lingga Regency and the main factors causing non-voting behavior in Kote Village, Lingga Regency. The research method used in this research is a descriptive qualitative method. Data collection was carried out through interviews with several informants who were related to the research. The results of the research show that the non-voting behavior carried out by the people of Kote Village is caused by several things, namely the attitude of the community who are less concerned about the ongoing Village Head Election which is based on the lack of influence of the Village Head Election on the community. Some communities find it difficult to contribute to village policy making and do not understand the ongoing village election system. Apart from that, there are people who believe that the Village Head candidate they support will win or lose in the ongoing Village Head Election so they feel there is no need to come to vote. However, the reason why most people in Kote Village do not vote is because of work factors that cannot be left behind due to economic needs and educational factors, especially students who study outside the area and are unable to return to Kote Village to carry out the Village Head election.